Long-Term Storage Effects on Stability of Aβ(1–40), Aβ(1–42), and Total Tau Proteins in Human Plasma Samples Measured with Immunomagnetic Reduction Assays - Chiu, Ming-Jang (Dement Geriatr Cogn Dis Extra, 2019)
BACKGROUND: The stability of Alzheimer's disease (AD) biomarkers in plasma, measured by immunomagnetic reduction (IMR) after long-term storage at −80°C, has not been established before. METHOD: Ninety-nine human plasma samples from 53 normal controls (NCs), 5 patients with amnestic mild cognitive impairment (aMCI), and 41 AD patients were collected. Each plasma sample was aliquoted and stored as single-use aliquots at −80°C. The baseline measurements for Aβ(1–40), Aβ(1–42), and total Tau protein (T-Tau) concentrations for each sample were done within 3 months of blood draw by IMR. They are referred to as baseline concentrations. A separate aliquot from each sample was assayed with IMR to assess the stability of the measured analytes during storage at −80°C between 1.1 and 5.4 years. This is referred to as a repeated result. RESULTS: IMR shows that plasma levels of Aβ(1–40) and Aβ(1–42) exhibit stability over 5-year storage at −80°C and that plasma levels of T-Tau are less stable (approximately 1.5 years). CONCLUSION: Although the measured concentrations of T-Tau in human plasma may alter during storage, the diagnostic utility of the results are only slightly affected when the product of Aβ(1–42) and T-Tau concentrations are used. The results show that the overall agreement between baseline and repeated measurements in the ability of discriminating NCs from aMCI/AD patients is higher than 80%.